Pancreaticojejunostomy with double-layer continuous suturing is associated with a lower risk of pancreatic fistula after pancreaticoduodenectomy: A comparative study. (January 2015) - Ji, Weiping; Shao, Zhuo; Zheng, Kailian; Wang, Juan; Song, Bin; Ma, Hongyun; Tang, Liang; Shi, Ligang; Wang, Yang; Li, Xinxing; Song, Bo; Zhang, Yijie; et al.
Abstract: Background : Postoperative pancreatic fistula (POPF) remains a leading cause of morbidity and mortality after pancreaticoduodenectomy (PD). Thus, a number of technical modifications regarding the pancreatoenteric anastomosis after PD have been proposed to reduce POPF rate. In this article we focused on evaluating whether the double layer continuous suture technique was better than the double layer interrupted suture technique in pancreatic–enteric anastomosis after PD.Material and methods : From 2012 to 2013, 114 patients (67 men and 47 women) underwent a pancreatic–enteric anastomosis after PD were analysed. There were 79 patients using the double layer continuous suture technique and 35 patients were using the double layer interrupted suture technique. The operation time, intraoperative blood loss, initial postoperative day of oral feeding, postoperative hospital stay and the presence of main early complications (pancreatic fistulas) were evaluated by chi-square test or unpaired t -test in this study.Results : Pancreatic fistulas occurred in patients with double layer continuous suture was 17.14%(6/35), and in those with interrupted suture was 39.24%(31/79) ( p  < 0.05). Grade A of POPF was found in 4 patients (4/35, 11.43%) of the double layer continuous suture group and in 5 patients (5/79, 6.33%) of the double layer interrupted suture group. Grade B of POPF was identified only in 1 patients (1/35, 2.83%) of the double layer continuous suture group and in 23 patients (23/79, 29.11%) of the double layer interrupted suture group. The presence of Grade C pancreatic fistulas was only documented in one patient in the double layer continuous suture group and 3 patients in the interrupted suture group. No operative or in-hospital deaths occurred.Conclusions : The double-layer continuous suturing after PD is safe, reliable, rapid, favorable and associated with a lower risk of pancreatic fistula than the double layer interrupted suture. Highlights: Suture ways influence the occurrence of postoperative pancreatic fistula (POPF). The double layer continuous suture technique can be safely used in Pancreaticojejunostomy. The double layer continuous suture technique leads to a lower risk of POPF.